Rehabilitating a Historical Coal Mine in Wangaloa, New Zealand - C M. Evans; D Thomas (The Australasian Institute of Mining and Metallurgy, 2006)
Solid EnergyÆs Wangaloa open cast coal mine was operated between 1945 - 1989, and remained closed and disused until 2001 when SENZ initiated a mine rehabilitation programme. It is nearing the final stages of physical and environmental rehabilitation, aimed at creating an aesthetically pleasing and useful landscape. The final goals of these efforts are to produce an area, which has recreational and educational value. SENZÆs holistic approach to rehabilitation has been undertaken, treating the entire historical mine footprint instead of focusing only on those disturbed areas and the minimum range of issues just to meet with legal compliance. Rehabilitation at the site has included overburden modification with an emphasis on stability, removal and replacement of unhealthy and invasive plant species, and an AgLime amendment to alter soil pH conditions, which would support native plant species. To date, most ongoing activities relate to final planting and plant upkeep, and maintenance of the landform including ongoing erosion control, pest control, environmental monitoring, and research. Environmental quality concerns at the site may be treated by using a combination of methods, including regrading and capping of acid-generating pyrites, soil treatment with AgLime, and passive wetland treatment within existing water courses. Following major works, the mine site area may be opened to the public for recreational activities, interpretive displays on historical mining activities, and observation and appreciation for otherwise unseen geological features. SENZÆs holistic approach to reclamation, rather than treating minor issues, will result in the former mine site being transformed into an asset and the environmental and financial liability associated with the closed mine being discharged. Former mine sites can be turned from environmental liabilities with no recreational or public value (and potentially dangerous to life) into sites that can be safely used by the public for recreational and educational purposes.